2022
DOI: 10.1161/circep.122.010926
|View full text |Cite
|
Sign up to set email alerts
|

Left Bundle Branch Pacing Postatrioventricular Junction Ablation for Atrial Fibrillation: Propensity Score Matching With His Bundle Pacing

Abstract: BACKGROUND: Left bundle branch pacing (LBBP) has emerged as a promising pacing modality to preserve physiological left ventricular activation; however, prospective data evaluating its long-term safety and efficacy in pacemaker-dependent patients following atrioventricular junction (AVJ) ablation are lacking. This study aimed to examine the feasibility, safety, and efficacy of LBBP in patients with atrial fibrillation and heart failure (HF) after AVJ ablation and compare LBBP with His bundle pacing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
5
19
0
Order By: Relevance
“…13,14 In the context of CSP, HBP and LBBAP were compared in two other recent observational studies. 15,16 In agreement with the findings of these studies, 15,16 we observed that, among the three pacing modalities compared, LBBAP was the one that required the lowest procedural and fluoroscopy times.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…13,14 In the context of CSP, HBP and LBBAP were compared in two other recent observational studies. 15,16 In agreement with the findings of these studies, 15,16 we observed that, among the three pacing modalities compared, LBBAP was the one that required the lowest procedural and fluoroscopy times.…”
Section: Discussionsupporting
confidence: 86%
“…[12][13][14] Recently, observational studies have reported that LBBAP combined with AVJA is technically feasible, associated with low capture thresholds, and, when compared with HBP, appears to be associated with a lower risk of complications. 15,16 Comparison data on complications risk between BVP and CSP collected in a prospective fashion are limited. Accordingly, we conducted a multicenter registry aimed to prospectively compare the clinical outcomes, including the rate and nature of device-related complications, between BVP and CSP in a cohort of patients undergoing A&P.…”
Section: Introductionmentioning
confidence: 99%
“…But no significant differences in death or HFH were observed between the HBP vs. LBBAP group. In the latest study including patients with AF after atrioventricular junction ablation, LBBP held higher successful implantation rates, better pacing parameters, and fewer lead-related complications compared with HBP, though both achieved similar improvement in clinical outcomes ( Cai et al, 2022 ). More recently, the first RCT (LBBP-RESYNC trail) to compare CRT efficacy between LBBP and BVP among heart failure patients with non-ischemic cardiomyopathy and LBBB found more improvement in LVEF by LBBP-CRT than BVP-CRT after 6-month follow-up ( Wang et al, 2022 ).…”
Section: Conduction System Pacing: the Evidence For Clinical Efficacymentioning
confidence: 99%
“…Previous studies and guidelines suggest that in patients with reduced LVEF and narrow QRS complex, BVP provides limited benefit ( Moss et al, 2009 ; Tracy et al, 2012 ). Compelling results of applying CSP in patients with PICM, RV pacing upgrading as well as AV node ablation in atrial fibrillation patients are accumulating ( Vijayaraman et al, 2017 ; Cai et al, 2022 ; Huang W. et al, 2022 ; Ivanovski et al, 2022 ). Hence, we expect that CSP may be a better option for primary and upgrading therapy in HF patients who have intact intraventricular conduction but need high RV pacing burden due to bradycardia or AV node ablation.…”
Section: Conduction System Pacing: the Evidence For Clinical Efficacymentioning
confidence: 99%
“…In this issue, Cai et al 15 provide exactly such data. The authors report a prospective registry of patients who underwent atrioventricular junction ablation and attempted LBBP for AF and heart failure, alongside a retrospective cohort of patients who underwent HBP and atrioventricular junction ablation over a longer but overlapping study period.…”
mentioning
confidence: 95%